2021
DOI: 10.1038/s41467-021-24677-6
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-defined leiomyosarcoma subtypes emerge years before diagnosis and determine patient survival

Abstract: Leiomyosarcomas (LMS) are genetically heterogeneous tumors differentiating along smooth muscle lines. Currently, LMS treatment is not informed by molecular subtyping and is associated with highly variable survival. While disease site continues to dictate clinical management, the contribution of genetic factors to LMS subtype, origins, and timing are unknown. Here we analyze 70 genomes and 130 transcriptomes of LMS, including multiple tumor regions and paired metastases. Molecular profiling highlight the very e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 60 publications
2
59
0
Order By: Relevance
“…However, it should be noted that methylation class prediction revealed substantial epigenetic differences between LMS and MFS, resulting in different class assignments with MFS cases clustering in the undifferentiated sarcoma class 57 . Although mutational landscape and analysis on the tumor evolution revealed that biallelic inactivation of TP53/RB1 are frequent and fundamental event in both MFS (Figures 4 and 5) and LMS, 6,58 in comparison with MFS genetics, LMS less frequently harbors alterations in CDKN2A (8% vs 30% in MFS) and NF1 (4% vs 22% in MFS), but more commonly affected DSB repair pathway (73.5% vs 32% in MFS). In MFS, various alterations in receptor tyrosine kinase (RTK)‐RAS‐PI3K cancer pathway (eg, KRAS , BRAF , PIK3CA and NF1 ) were more frequently detected (36.2% vs not described in LMS), which may result in inter‐ and intratumor heterogeneity of MFS but offer therapeutic windows.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that methylation class prediction revealed substantial epigenetic differences between LMS and MFS, resulting in different class assignments with MFS cases clustering in the undifferentiated sarcoma class 57 . Although mutational landscape and analysis on the tumor evolution revealed that biallelic inactivation of TP53/RB1 are frequent and fundamental event in both MFS (Figures 4 and 5) and LMS, 6,58 in comparison with MFS genetics, LMS less frequently harbors alterations in CDKN2A (8% vs 30% in MFS) and NF1 (4% vs 22% in MFS), but more commonly affected DSB repair pathway (73.5% vs 32% in MFS). In MFS, various alterations in receptor tyrosine kinase (RTK)‐RAS‐PI3K cancer pathway (eg, KRAS , BRAF , PIK3CA and NF1 ) were more frequently detected (36.2% vs not described in LMS), which may result in inter‐ and intratumor heterogeneity of MFS but offer therapeutic windows.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of desmin expression should be investigated in leiomyosarcoma as a potential marker of more aggressive behavior. Although the importance of histologic and molecular subtype of sarcomas has been demonstrated in people, 1,21,50 our study emphasizes the need for continued efforts in veterinary species to ensure that these subtypes are accurately classified to potentially predict behavior and guide treatment more definitively. Future studies with alternative tools such as electron microscopy and molecular characterization in addition to IHC staining are required in veterinary medicine to better document the spectrum of IHC staining variation and clinical behavior of sarcoma subtypes, including non-visceral SMA-positive mesenchymal tumors such as leiomyosarcomas and myofibroblastic tumors.…”
Section: Discussionmentioning
confidence: 94%
“…Early mutations in TP53 seem to exist in most leiomyosarcomas (LMS) cases, whereas other mutations including ATRX deletions and Wnt/b-catenin alternations determine the genetic diversity of LMS (14). In another study, inactivation of TP53 and RB1 appears to be a universal phenomenon, together with vast number of copy number variations (CNVs), mutational heterogeneity, and wholegenome duplication.…”
Section: Mechanism and Diagnosismentioning
confidence: 99%
“…Considering the vast amount of genomic data for malignancies, there are plenty of genetic differences among patients bearing the same type of sarcoma, sometimes making it possible for us to divide them into different subtypes with their respective clinical features and prognosis. Research showed that LMS subtype appeared in an early period of tumor and retained thereafter (14), enhancing the importance of subtype differentiation in malignancies of all stages.…”
Section: Subtypes Clusteringmentioning
confidence: 99%
See 1 more Smart Citation